Human capital investment, new firm creation and venture capital - Sevilir, Merih (Journal of Financial Intermediation, 2010)
This paper studies the relation between firm investment in general human capital, new firm creation and financial development for new firm financing, such as the existence of a venture capital industry. On one hand, firm investment in general human capital leads employees to generate new innovative ideas for starting their own firm. Since employees need a venture capitalist to start their new firm, firm investment in general human capital encourages the creation of venture capitalists by increasing the need for their services, such as providing advice and monitoring. On the other hand, as new firm financing becomes available, firms’ willingness to invest in general human capital increases, and as a by-product, the creation of employee-founded and venture capital-backed new firms increases in the economy. Hence, our model provides a rational explanation for the emergence of new firms created by employees of established firms, which represents one of the most common type of new firms in many industries.